(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate pregnancy outcomes of pregnant women with premature rupture of membranes at gestational age from 24 to 34 weeks at Hanoi Obstetrics and Gynecology Hospital. Subjects and methods: A retrospective cross-sectional descriptive study on 217 pregnant women with preterm rupture of membranes at gestational age from 24 weeks 0 day to 33 weeks 6 days at Hanoi Obstetrics and Gynecology Hospital from January 2022 to December 2022. Results: The average age of pregnant women was 30.1±6.1. Premature rupture of membranes is common in pregnant women with a history of previous cesarean section (33.2%), history of abortion (20.7%), and miscarriage and stillbirth (15.6%). Fetuses weighing from 1500 to 2500g account for the highest proportion (70.5%). 100% of children weighed <1000gr Apgar in the first minute <7 points. The lower the AFI, the higher the rate of low first-minute Apgar is. 100% of babies were born weighing less than 1500g and 94% of amniotic fluid loss require neonatal resuscitation. 88.9% of children were taken to neonatal resuscitation: 44.2% received NCPAP continuous positive pressure ventilation. There were 43 children who did not use antibiotics (20.7%). 5 severe cases were transferred to Children’s Hospital for treatment (2.4%). Neonatal mortality accounts for 7.8%, most of which are very premature (24-28 weeks). Conclusion: The fetus weighs mainly 1500-2000g. Weight and amniotic fluid index affect the first minute Apgar index. In cases of babies <1500g and no amniotic fluid at birth, most neonatal resuscitation is required. A small percentage of patients are transferred to a pediatric hospital for treatment. Neonatal deaths are all very premature fetuses (24-28 weeks).